فاعلية برنامج مقترح لتدريس الثقافة القانونية لدئ طلاب الصف العاشر من التعليم الأساسي في محافظة الدا خلية بسلطنة عمان - Hinai Wail Saif Salim (Universiti Sains Islam Malaysia, 2024)
The aim of this study was to investigate the effectiveness of a proposed program of enhancing the awareness of social-legal curricula aspects for the tenth grade of basic education in the Sultanate of Oman.This research combines two basic dimensions: analytical, descriptive and applied. The first dimension dealt with the analysis of the existing levels of teaching the legal culture program in the study sample. The first dimension also analyses the requirements for developing the proposed legal culture enhancement program and its characteristics according to the ADDIE model. The first dimension ended with the development of the proposed legal culture development program for tenth grade students in basic education in Oman. The second dimension dealt with the experimental aspects, by measuring the differences between the experimental and control groups in the achievement legal culture aspects and measuring the differences between the experimental and control groups in the scale of the legal culture attitudea due to using proposed legal culture program. This study used two methods, namely: (descriptive, analytical, experimental method. The descriptive and analytical aeploratory approach addressed a the authenticity of research problem where the interview was used to survey the views of randomly selected educational supervisors, teachers and faculty members n=(30) in the field of curricula and methods of teaching social studies. This interview focused on exploring the suggestions of educational supervisors and their views on the need to include aspects of legal culture in the curricula of social studies so that enhance the level of legal awareness among the students. The experimental practices examined the effectiveness of the proposed program and its effect on teaching the legal culture for the tenth grade students in basic education. The experimental sample consisted of two experimental groups and two control groups. The two experimental groups studied was treated using the proposed program,while the control group was treated using the tradisional ordinary course. The tools used in this research were: a list of legal culture aspects, achievement tests, the proposed educational program and a scales of attitudes towards legal culture. The research used attitude scales and the achievement test before and after so as to reveal the affectiveness of the proposed program developing awareness of the proposed legal culture.The results of this research showed the effectiveness of the proposed program of enhancing the awareness of socio-legal aspects for the tenth grade education in the Sultanate of Oman. The research recommended the need to include aspects of legal culture in oder to enhance the level of socio-legal awareness among the students.